Ingestive behavior of cattle in different production system – a systematic review of scientific studies (Research, Society and Development, 2020)
The ingestive behavior study is an important tool for diet evaluation and the relationship of the animal with production system. The objective this study was to analyze the ingestive behavior of cattle in grazing and feedlot for some variables, under experimental conditions. Scientific papers published from September 2004 to March 2018 were analyzed using the systematic review framework. Of the 88 papers initially selected, after applying new selection criteria, 35 articles constituted the information bank, with 153 information and 1079 cattle in experiments. The study showed statistical difference (P